1996
DOI: 10.1136/gut.38.5.775
|View full text |Cite
|
Sign up to set email alerts
|

Roles of gall bladder emptying and intestinal transit in the pathogenesis of octreotide induced gall bladder stones.

Abstract: Background-Octreotide treatment of acromegalic patients increases the 0/0 deoxycholic acid conjugates and the cholesterol saturation ofgall bladder bile, and induces gall stone formation. Aims-To study the roles of gall bladder emptying and intestinal transit in these phenomena. Methods and patients-Gall bladder emptying and mouth to caecum transit was measured in (a) control subjects and acromegalic patients given saline or 50 Kug ofoctreotide, and (b) acromegalic patients taking long term octreotide. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 48 publications
3
42
1
Order By: Relevance
“…The postulated carcinogen in this case is intralumenal bile acids which have undergone bacterial deconjugation in the right colon. These compounds, such as deoxycholic acid (DCA), have been strongly implicated in the development of sporadic colonic cancer and are increased in patients with acromegaly due in part to the prolonged colonic transit occurring in this condition (9). Thus, the increased IGF-I levels in acromegaly would increase the chances of survival of cells with damaged DNA in response to the elevated DCA levels, rather than the cells undergoing the normal protective apoptotic response.…”
Section: Evidence Implicating Igf-i In Cancermentioning
confidence: 99%
“…The postulated carcinogen in this case is intralumenal bile acids which have undergone bacterial deconjugation in the right colon. These compounds, such as deoxycholic acid (DCA), have been strongly implicated in the development of sporadic colonic cancer and are increased in patients with acromegaly due in part to the prolonged colonic transit occurring in this condition (9). Thus, the increased IGF-I levels in acromegaly would increase the chances of survival of cells with damaged DNA in response to the elevated DCA levels, rather than the cells undergoing the normal protective apoptotic response.…”
Section: Evidence Implicating Igf-i In Cancermentioning
confidence: 99%
“…Resmini et al revealed prolonged oro-cecal transit time and small intestinal bacterial overgrowth in acromegaly patients [5], and Catnach et al found that gall bladder motor function was severely impaired in untreated acromegaly patients [17]. In another study reporting on gall bladder emptying and small intestinal transit in acromegaly patients, Hussaini et al showed that intestinal transit and gall bladder volume were significantly different between acromegaly patients and controls [18]. Our results contribute to previous studies by indicating motility abnormalities of the oesophagus and by suggesting that acromegaly could have unfavourable effects on oesophageal motility through the mechanisms of reduced percentage and duration of LES relaxation in patients without any clinical gastrointestinal symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…In the context of gallstones, small bowel transit time becomes progressively longer throughout pregnancy, eventually returning to normal after delivery (23). Impaired small bowel transit has been shown to be a factor in gallstone disease (22) and occurs during octoreotide therapy, which is known to induce gallstones (27,28). Prolonged large bowel transit has also been shown to be a factor in gallstone disease (29,30); however, studies of large bowel transit during pregnancy have produced conflicting results (23).…”
Section: Physiological Changes In the Biliarymentioning
confidence: 99%
“…It was also a factor in stone recurrence following dissolution (25). Other conditions inducing gallbladder stasis, such as parenteral alimentation (26) or octreotide therapy (27), were proven to be lithogenic. Impaired motility of the gastrointestinal tract: Pregnancy induces hypomotility throughout the gastrointestinal tract, probably via high progesterone levels.…”
Section: Physiological Changes In the Biliarymentioning
confidence: 99%